Storage root yield of sweetpotato as influenced by sweetpotato leaf curl virus and its interaction with sweetpotato feathery mottle virus and sweetpotato chlorotic stunt virus in Kenya - Wanjala, Bramwel W.; Ateka, E.M.; Miano, D.W.; Low, Jan W.; Kreuze, Jan F. (Scientific Societies, 2020)
In this study, the effect of a Kenyan strain of Sweetpotato leaf curl virus (SPLCV) and its interactions with Sweetpotato feathery mottle virus (SPFMV) and Sweetpotato chlorotic stunt virus (SPCSV) on root yield was determined. Trials were performed during two seasons using varieties Kakamega and Ejumula and contrasting in their resistance to sweetpotato virus disease in a randomized complete block design with 16 treatments replicated three times. The treatments included plants graft inoculated with SPLCV, SPFMV, and SPCSV alone and in possible dual or triple combinations. Yield and yield-related parameters were evaluated at harvest. The results showed marked differences in the effect of SPLCV infection on the two varieties. Ejumula, which is highly susceptible to SPFMV and SPCSV, suffered no significant yield loss from SPLCV infection, whereas Kakamega, which is moderately resistant to SPFMV and SPCSV, suffered an average of 47% yield loss from SPLCV, despite only mild symptoms occurring in both varieties. These results highlight the variability in yield response to SPLCV between sweetpotato cultivars as well as a lack of correlation of SPLCV-related symptoms with yield reduction. In addition, they underline the lack of correlation between resistance to the RNA viruses SPCSV and SPFMV and the DNA virus SPLCV.